Meningkatkan Efektivitas Pembelajaran Melalui Tata Kelola Ruang Kelas yang Optimal - Nurista, Annisa Salsabila; Khoerunnisa, Hijri; Luhukay, Michelya Zabrina; Nurmalasari, Ulfi; Mustikaati, Wina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Classroom governance is the process of planning, organizing, and managing the learning environment within the classroom with the aim of creating a conducive and comfortable atmosphere for students, thereby enabling the achievement of learning objectives. The arrangement of physical space, behavior management, and the optimal use of resources can enhance students’ concentration and learning outcomes.This article discusses the improvement of learning effectiveness through optimal classroom management while also providing an understanding of the importance of effective classroom governance in the learning process. This study employs a descriptive qualitative approach to understand the effectiveness and role of classroom governance in education. Data collection was conducted using a single primary technique, namely literature review or theoretical study. The findings reveal that classroom governance significantly influences the effectiveness of learning and student performance.